ANALISIS PENGARUH RETURN ON ASSET, RETURN ON EQUITY, SUKU BUNGA DAN INFLASI TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Suyanto Suyanto; Anwar Effendi (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2016)
This study was conducted to investigate the effect of return on assets, return on equity, interest rate and inflation on the price of shares in the Sub-Sector Food and Beverage at the Stock Exchange in 2012-2014. The study population is a company Sub Sector Food and Beverage at the Stock Exchange for the period of the year 2012 to te year 2014 with 11 companies samples by using purposive sampling method.The method used is descriptive and verification methods, because of the variables to be explored relationship as well as the aim to present a picture of a structured, factual, and accurate information on the facts and the relationship between the variables studied, namely the influence of return on assets (ROA) , return on equity (ROE),Â interest rate and inflation on stock prices.The results showed that there are significant influence between the variables X1 (return on assets) to variable Y (the stock price), significant relationship between the variables X2 (return on equity) to variable Y (the stock price), significant negative influence between the variables X3 (interest rate) to variable Y (the stock price), and relationship between the variables X3 (inflation) to variable Y (the stock price) significant as well.Each variable X1 (return on assets), X2 (return on equity), X3 (interest rate) and variable X4 (inflation) are jointly significant effect to variable Y (the stock price).Â Key words:return on assets, return on equity, interest rate, inflation, stock prices